Determination of some β‐Blockers by Electrochemical Detection on Polycrstalline Gold Electrode after Solid Phase Extraction (SPE). Issue 5 (21st December 2015) - Casella, Innocenzo G.; Bonito, Rosa; Contursi, Michela
Abstract: The electroanalytical characterization and determination of three selected β‐blocker agents, namely propranolol, atenolol and nadolol using cyclic voltammetry and differential pulse voltammetry (DPV) in phosphate buffer solution (pH 2.5) plus 22 % acetonitrile (ACN), was described. The analytes were characterized through their electrooxidation processes on polycrystalline gold electrodes. The analytical determination of the selected molecules was performed using the differential pulse voltammetry (DPV) at pH 2.5. Under DPV conditions, the detection limits (LODs) ranged between 5 μM and 20 μM for propranolol and atenolol, respectively. For all investigated molecules, two well‐defined ranges of linearity Ip vs analyte concentration have been identified which correspond to specific calibration parameters. Calibration graphs (Ip vs concentration) considered in the first interval of linearity, shown correlation coefficients >0.99. A solid phase extraction (SPE) procedure using a polymeric mixed‐mode cationic sorbent (Strata‐X‐C), was studied and optimized. The proposed DPV‐SPE method was successfully applied for the determination of propranolol in several pharmaceutical formulations and urine sample, with results in close agreement with those obtained using traditional liquid chromatography technique coupled with spectrophotometric detection. Abstract :